2010
DOI: 10.1111/j.1365-2559.2010.03534.x
|View full text |Cite
|
Sign up to set email alerts
|

Stromal CD10 expression and relationship to the E‐cadherin/β‐catenin complex in breast carcinoma

Abstract: Stromal CD10 expression in IDC may constitute an important prognostic marker. Stromal CD10 expression with associated aggressive features might be related to aberrant beta-catenin expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
23
1
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 33 publications
(95 reference statements)
9
23
1
6
Order By: Relevance
“…Moreover, it has been reported that carcinoma of the breast that not expressed stromal CD 10 behave better, both clinically and biologically than invasive breast carcinoma that expressed it. 7,8,[13][14][15][16][17][18][19][20][21] In the present study, stromal CD10 expression was found in 70.4% of the cases (including 46.2% weakly positive and 24.2% strongly positive specimens) which is close to the frequency observed by other studies, while higher than others as seen below. Makretsov et al 13 found stromal CD10 expression in 79% of invasive breast carcinomas.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, it has been reported that carcinoma of the breast that not expressed stromal CD 10 behave better, both clinically and biologically than invasive breast carcinoma that expressed it. 7,8,[13][14][15][16][17][18][19][20][21] In the present study, stromal CD10 expression was found in 70.4% of the cases (including 46.2% weakly positive and 24.2% strongly positive specimens) which is close to the frequency observed by other studies, while higher than others as seen below. Makretsov et al 13 found stromal CD10 expression in 79% of invasive breast carcinomas.…”
Section: Resultssupporting
confidence: 88%
“…Also, differences in the population group, diversity of risk habits and variation of genetic predisposition may contribute to that wide range of stromal CD10 expression that reported in different countries. [13][14][15][16][17][18][19][20][21][22][23] Similar to this study, Makretsov et al, 13 Iwaya et al, 18 Masaki et al, 17 Puri et al, 19 Sadaka et al 20 and Hosni et al 14 failed to show a significant correlation between between tumor size and CD10 expression. While Kim et al ., 21 Mohammadizadeh et al 15 and Taghizadeh-Kermani et al 16 have found the opposite.…”
Section: Resultssupporting
confidence: 73%
“…Since then, CD10 expression besides lymphoblastic leukemia and non-Hodgkin's lymphoma of B-cell line has also been observed in number of cancers as gastric, lung, breast prostate and colorectal. The observations showed correlation between level of CD10 expression and higher histological grade, larger tumor size, vascular invasion and overall survival rate patients with solid tumors [4].…”
mentioning
confidence: 83%
“…Alteration of molecular biological markers in tumor tissues has become an important part in predicting the prognosis of patients with BC and seemed more specific than markers currently used in clinical such as TNM stage, weight loss and lymph node metastasis. There are many reports about the prognostic significance of β-catenin in BC (Lin et al, 2000;Gillett et al, 2001;Lim and Lee, 2002;Chung et al, 2004;Dolled-Filhart et al, 2006;Nakopoulou et al, 2006;Park et al, 2007;Fanelli et al, 2008;Paredes et al, 2008;Khramtsov et al, 2010;Kim et al, 2010;Logullo et al, 2010;Lopez-Knowles et al, 2010;Geyer et al, 2011;Cheng et al, 2012;Mukherjee et al, 2012;Xu et al, 2012;Ho et al, 2013;Pang et al, 2013;Weissenbacher et al, 2013;Li et al, 2014). However, results were inconsistent.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Tumor cells escaping from the primary tumor is the 1 Chung et al, 2004;Park et al, 2007;Fanelli et al, 2008;Kim et al, 2010;Logullo et al, 2010;Lopez-Knowles et al, 2010;Xu et al, 2012;Ho et al, 2013;Pang et al, 2013). The discrepancies in conclusions may attribute to some of the defects in individual study such as small sample size or low statistical power.…”
Section: Introductionmentioning
confidence: 99%